Study of the clinical and functional characteristics of asthmatic children with obstructive sleep apnea - Nguyen-Hoang Y; Nguyen-Thi-Dieu T; Duong-Quy S (Journal of Asthma and Allergy, 2017)
Yen Nguyen-Hoang,1 Thuy Nguyen-Thi-Dieu,2 Sy Duong-Quy3–5 1Department of Pediatrics, Phu Tho General Hospital, Phu Tho Province, 2Department of Pediatrics, Hanoi Medical University, Hanoi, 3Biomedical Research Center, Lam Dong Medical College, Dalat, Vietnam; 4Department of Physiology and Lung Function Testing, Cochin Hospital, Paris Descartes University, Paris, France; 5Division of Asthma and Immuno-Allergology, Hershey Medical Center, Penn State Medical College, Hershey, PA, USA Background and objective: The obstructive sleep apnea (OSA) is a common respiratory disorder in children, especially those at preschool and school ages. This study aimed to describe the characteristics of asthmatic children with OSA and the symptoms for a high risk of OSA. Subjects and methods: It was a prospective and descriptive study. The data of asthmatic children including medical history, clinical examination, blood tests, spirometry, exhaled nitric oxide (NO), and respiratory polygraphy were registered for analyses. Results: Eighty-five asthmatic children with a mean age of 9.5 ± 2.1 years were included. The prevalence of OSA was 65.9% (56/85) in study subjects. The prevalence of severe OSA in children with moderate asthma was significantly higher than intermittent and mild asthma. The percentage of asthmatic children with OSA who had snoring, sleep disturbance, and nocturnal sweats was significantly higher than that of asthmatic children without OSA (48.2% vs 17.2%, 71.4% vs 27.5%, and 55.1% vs 31.0%, respectively). The presence of allergic rhinitis and snoring was associated significantly with a high probability for the presence of OSA. Conclusion: Children with asthma have a risk of OSA. Asthmatic children with suggested symptoms such as snoring or waking up at night should be screened for OSA. Keywords: asthma, OSA, snoring, allergic rhinitis